Masa Pertumbuhan dan Perkembangan Pendidikan Islam pada Masa Khulafaur Rasyidin - Akhmad Rifansyah; Ahmad Muhajir; Achmad Khafi; Mahfud Ifendi (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Islamic education during the Khulafaur Rasyidin period (632-661 AD) had an important role in forming the foundations of the Islamic education system during the Khulafaur Rasyidin period, which included the period of leadership of the first four caliphs after the death of the Prophet Muhammad SAW. This research aims to examine in more depth the growth and development of Islamic education during the time of Khulafaur Rasyidin, including the role of the caliphs in supporting the education system and its impact on Islamic society at that time. The author uses a qualitative method with the type of library research. This method aims to explore information in depth from relevant library sources, such as books, scientific articles, journals and other documents. As for the results of this research, the growth and development of Islamic education during the time of Khulafaur Rasyidin focused on teaching the Qur'an and Hadith, the development of educational centers during the time of Abu Bakar, Kutab educational institutions (primary schools) experienced significant progress, during the time of Caliph Umar bin Khattab ra., the social and political situation was in a stable condition and Islamic power was increasingly expanding, where several friends were appointed as teachers in each area they occupied. During the time of Usman ibn Affan the development of Islamic education, both in terms of institutions and materials, was basically not much different from previously. During the time of Ali bin Abi Talib, the development of education did not show significant progress. This was caused by the chaotic political situation and various rebellions that occurred, so that Ali's government was unstable and focused more on efforts to resolve conflicts and maintain political stability.